2017
DOI: 10.18632/oncotarget.17836
|View full text |Cite
|
Sign up to set email alerts
|

Soluble antigens from the neurotropic pathogenAngiostrongylus cantonensisdirectly induce thymus atrophy in a mouse model

Abstract: The nematode Angiostrongylus cantonensis (A.C.) is a neurotropic pathogen; stage-III larva invade the human (non-permissive host) central nervous system (CNS) to cause eosinophilic meningitis or meningoencephalitis accompanied by immunosuppression. In an A.C.-infectedmouse (another non-permissive host) model, CNS damage-associated T cell immune deficiency and severe inflammation were proposed to result from activation of the hypothalamic-pituitary-adrenal (HPA) axis. However, glucocorticoids are anti-inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
3
0
2
Order By: Relevance
“…Similarly, Liu et al. ( 97 ) observed that soluble antigen from A. cantonensis can lead to apoptosis of thymic stromal cells and thymocytes. In addition, F. tularensis is also found in thymus tissue during infection ( 78 ).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Similarly, Liu et al. ( 97 ) observed that soluble antigen from A. cantonensis can lead to apoptosis of thymic stromal cells and thymocytes. In addition, F. tularensis is also found in thymus tissue during infection ( 78 ).…”
Section: Discussionmentioning
confidence: 86%
“…Increasing research evidence indicates the close and complex relationship between host and exosomes originating from pathogens. Interestingly, it is mentioned above that the administration of the soluble antigen of A. cantonensis into the thymus of mice can cause obvious thymic atrophy, as for mice directly infected with A. cantonensis ( 97 ). Given that soluble antigens of A. cantonensis may break down during a long journey from the brain to the thymus, we reasonably speculate that the transport of soluble antigens should rely on a more effective vector, with exosomes the suitable choice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finalmente, otros resultados mostraron algunos mecanismos poco dilucidados en nuestro medio, producido por la infección del helminto. Tal es el caso de un artículo del 2017 que indica la posible atrofia del timo en modelos experimentales 18 y otro artículo en PlusOne que le atribuye a un proteosoma la regulación fundamental en el proceso de inducción de la infección en el sistema nervioso central 19 .…”
Section: Fisiopatologíaunclassified
“…El estudio de Chen y Wang 18 en ratones, arroja que los productos de excreción/secreción ☞ http://archivosdeneurociencias.com MENINGOENCEFALITIS EOSINOFÍLICA POR ANGIOSTRONGYLUS CANTONENSIS del quinto estadio larval de Angiostrongylus cantonensis estimulan la activación de astrocitos y la generación de citocinas (Interleucina-1a e Interleucina-6) con el empleo del Factor nuclear de trascripción-Kb (NF kB) y de la vía de la proteína señalizadora Sonic Hedgehog (Shh). La prevención de la enfermedad cuando se viaja a áreas endémicas es de gran relevancia.…”
Section: Tratamiento De Meningoencefalitis Eosinofílicaunclassified